2018
DOI: 10.3389/fpsyg.2018.00857
|View full text |Cite
|
Sign up to set email alerts
|

How Does Social Behavior Relate to Both Grades and Achievement Scores?

Abstract: Prosocial behavior and peer problems are an important correlate of academic development; however, these effects vary by achievement measures and social behaviors. In this paper, we examined data from the German National Education Panel Study (NEPS), and we use structural equation modeling (SEM) to model the effects of prosocial behavior and peer problems on grades and competencies for both math (n = 3,310) and reading (n = 3,308) in grades 5 and 7. Our models account for the moderating effect of both gender an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 33 publications
0
23
2
Order By: Relevance
“…Similarly, Palmu et al [16] highlighted that externalizing behavior (broadband scale) was associated with lower academic grades. Similarly, DeVries et al [17] concluded that peer problems (narrowband scale) are negatively associated with academic grades. Higher internalizing and externalizing behavior (broadband scales) were linked to lower scholastic performance [18].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, Palmu et al [16] highlighted that externalizing behavior (broadband scale) was associated with lower academic grades. Similarly, DeVries et al [17] concluded that peer problems (narrowband scale) are negatively associated with academic grades. Higher internalizing and externalizing behavior (broadband scales) were linked to lower scholastic performance [18].…”
Section: Introductionmentioning
confidence: 95%
“…Although the originally proposed 5-factor structure of the SDQ (5 narrowband subscales) is often applied in research [ 12 , 17 , 19 , 20 , 22 , 23 ], the narrowband subscales are sometimes subsumed into broadband behavior scales (internalizing and externalizing behavior) [ 4 , 14 , 15 , 18 , 21 , 24 ], which has resulted in an ongoing controversy, not only in educational research, regarding the factor structure of the SDQ [ 25 27 ]. This controversy implies a discussion about the usefulness of broadband and narrowband scales of behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This study is consistent with findings Hoff, Laursen, & Tardif (2002), suggesting that higher socioeconomic strata change more in responding to changes in child development in contrast to parents in lower socio-economic strata. In the opinion of Devries, Rathmann, & Gebhardt (2018), states that children with higher economies tend to show fewer social problems and more prosocial behavior.…”
Section: There Is An Influence Of Income Levels and Children's Socialmentioning
confidence: 99%
“…Migrant background and low SES have been repeatedly linked to worse educational outcomes in both language and math skills. The link between a lower SES and poorer education outcomes has been demonstrated in many countries around the world (White, 1982;Lekholm and Cliffordson, 2008;Currie, 2009;Björklund and Salvanes, 2011;Rambo-Hernandez and McCoach, 2014;Sirin, 2016;DeVries et al, 2018). Furthermore, recent studies have indicated that income levels and job categorization are weaker correlates of cognitive function than parental education levels (Eilertsen et al, 2016) while parental educational behavior is a better indicator (Rindermann and Baumeister, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…1) How do lower parental education levels and second language learning effect the development of reading and math competency in secondary school? We expect that both of these factors will negatively impact competency gain in both reading and math in seventh to ninth grade (Solari et al, 2014;Gebhardt et al, 2015;DeVries et al, 2018). 2) How does the use of individualized assignments, group work, and discussions effect the development of reading and math competency in secondary schools?…”
Section: Introductionmentioning
confidence: 99%